Proceedings 20th IEEE International Parallel &Amp; Distributed Processing Symposium 2006
DOI: 10.1109/ipdps.2006.1639431
|View full text |Cite
|
Sign up to set email alerts
|

Performance and power analysis of time-multiplexed execution on dynamically reconfigurable processor

Abstract: Dynamically Reconfigurable Processor (DRP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Since the practical use of them has just started, the architectural trade-off has not been well analyzed qualitatively. However, some practical analysis results has been reported recently [7], [18], and in the near future, the optimal structure will be selected automatically when the target application and SoC are fixed.…”
Section: Resultsmentioning
confidence: 99%
“…Since the practical use of them has just started, the architectural trade-off has not been well analyzed qualitatively. However, some practical analysis results has been reported recently [7], [18], and in the near future, the optimal structure will be selected automatically when the target application and SoC are fixed.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hasegawa [1], each implementation has an optimum context size (the number of tiles) where the performance becomes optimum. Other context sizes no matter whether they are smaller or larger than the optimum one result in performance degradation.…”
Section: Drp Architecturementioning
confidence: 99%
“…PE functionality, word bit width, the number of hardware contexts, the total amount of wiring resource, and the size of PE array itself are the examples. Our performance evaluation results revealed that the optimal PE array size considering the area and power consumption is different by each application [5]. Thus, there is no all-around architecture in DRPAs, and the structures should be configurable or customizable for their main target applications.…”
Section: Introductionmentioning
confidence: 99%